Integration of Technology In Public Services As An Effort to Enhance Government Organizational Resilience In Indonesia - Salam, Rudi; Asmar; Rosalin, Sovia (Jurnal Pallangga Praja (JPP), 2025)
Digital transformation has become a strategic necessity in strengthening the resilience of government organizations, especially in the face of health crises, natural disasters, and socio-economic pressures. This study aims to analyze how the integration of technology in public services contributes to enhancing organizational resilience in Indonesia’s public sector. A qualitative approach was employed using a case study design focused on a government institution implementing Electronic-Based Government Systems (SPBE). Data collection techniques included in-depth interviews, policy document analysis, and participatory observation. The findings reveal that technological integration through SPBE and digital platforms has improved service continuity, enhanced institutional adaptive capacity, and fostered faster decision-making and cross-sectoral collaboration. However, challenges such as digital infrastructure disparities, uneven digital literacy, and fragmented policy coordination between central and local governments remain significant barriers. The study concludes that technology must be strategically positioned as a long-term component in building public sector resilience.